Tinnitus: Characteristics, Need for Therapy, and Therapeutic Outcomes; Results of an International Patient Initiated Platform - Smit, Adriana L.; Vesala, Markku; Goedhart, Hazel; Eijden, Job van; Wempe, Christiaan; Stegeman, Inge (Frontiers in Neurology, 2022)
Introduction So far, there is a gap of knowledge about factors influencing the impact of tinnitus, the need for treatment as well as the experienced effect of regular and alternative tinnitus therapies. In this study we analysed the need for treatment and the outcomes of these treatments in an international patient initiated tinnitus platform. Material and Methods Two surveys were undertaken at an online tinnitus patient support community (www.tinnitustalk.com). The surveys were aimed at 1) used tinnitus treatment and outcomes 2) and the factors that influence tinnitus. Univariable logistic and linear regression was used to calculate the relation between factors and tinnitus impact as well as the relation with used tinnitus treatments and outcomes. Results Of the participants to the first survey (n=5017), 2914 (58.1 %) used one or more tinnitus therapies, most commonly self-administered sound therapy (n=1562 (31.1%)) and supplements/herbal medicines n=1157 (23.1 %)). Being female (OR 0.83 (95%CI 0.74-0.93, p<0.01)), tinnitus impact, and some degrees of hearing loss and hyperacusis were all statistically significantly associated with higher odds of having tinnitus treatment. Out of the second survey (n= 6115) it was found that patient, physical and psychological factors were statistically significantly related to tinnitus impact. Conclusion In this study we demonstrated the usage and experience of (multiple) tinnitus therapy of those affected. Several patient, physical and psychological characteristics were found to be related to tinnitus impact and therapy usage. These outcomes might function as a next step to find personalized treatment and to improve tinnitus health care.